Tourism and Study Abroad Options: The Use of Sources of Information by Indonesian Postgraduate Students to Choose an Overases University - Kusumawati, Andriani (Journal of International Students, 2020)
How prospective postgraduate students make a decision about overseas universities for their study and tourism remains scarcely reported. This qualitative study examines how Indonesian students explore information that influences their decision to choose an overseas university. Anchored in an interpretative paradigm, data were collected through semi-structured interviews and a qualitative questionnaire distributed to 19 Indonesian postgraduate students who just completed their studies in six different countries. Findings showed that university websites, social media, and advice from the reference groups facilitated mostly by the internet are valuable information sources considered by the students. Finally, implications and recommendations are presented for future studies.